Perceived public stigma and perceived public exposure by persons living with bipolar disorder: A qualitative study. (March 2023) - Favre, Sophie; Aubry, Jean-Michel; Richard-Lepouriel, Hélène
Background: Stigma impact the lives of persons living with bipolar disorder. Aim: The aim of this study was to explore how perceived public stigma is described by people living with bipolar disorder and examine the links between perceived public stigma and perceived public exposure. Method: Face-to-face in-depth interviews were conducted in a purposive sample of euthymic people living with bipolar disorder recruited in a mood disorder ambulatory unit. Results: Thematic analysis of the transcript yielded five independent themes that were related to perceived public stigma. Perceived public stigma of bipolar disorder was modeled as comprising the three elements of public stigmas (stereotype, prejudice, and discrimination), with the addition of public exposure as a core component. Conclusion: The representation of bipolar disorder in society via newspapers, films/TV series, conferences, and celebrity self-disclosures is considered to have multiple impacts. People living with bipolar disorder have also reported a perceived public stigma of bipolar disorder that has both specific features and characteristics of general mental illness.